The Influence of the STEAM Learning Model on Mathematics Learning Outcomes in Percent Material - Annisa Khairah; Sapri, Sapri; Siregar, Lailatun Nur Kamalia (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2023)
The aim of this research is to determine the effect of the STEAM (Science, Technology, Engineering, Art and Mathematics) learning model on mathematics learning outcomes in percent material in class IV SDIT Al-Fauzi, Medan City. This research uses quantitative field research methods and uses a pre-test and post-test control group design. 22 students from class IV-A were used as the control class and 22 students from class IV-B were used as the experimental class. Multiple choice test instruments are used to determine students' level of knowledge. The t-test is used to analyze research hypothesis data. The one-way anova test is used to analysis homogeneity data. By using one-way analysis of variance with a significance level of 0.05, the sig value is 0.000, which means 0.000 is less than 0.05. This situation shows that the STEAM learning model has a significant impact. In the experimental class, students obtained an average learning result of 81.45 with a difference in pre-test and post-test scores of 52.04. Meanwhile in the control class, students obtained an average learning outcome of 67.90. Therefore, the application of the STEAM model has a significant impact on the learning outcomes of students at SDIT Al-Fauzi Medan City in mathematics learning.